Low temperature synthesized SrMoO4:Eu3+ nanophosphors functionalized with ethylene glycol: A comparative study of synthesize route, morphology, luminescence and annealing. (July 2018) - Soni, Abhishek Kumar; Joshi, Rashmi; Jangid, Krishna; Tewari, R.; Ningthoujam, Raghumani Singh
Graphical abstract: Highlights: Tetragonal SrMoO4 :Eu 3+ downconverting phosphors functionalized with ethylene glycol have been synthesized via three different preparation techniques (urea hydrolysis, ammonia hydrolysis and hydrothermal methods). For the first time, a comparative study of synthesized route, morphology, luminescence and annealing has been given in detail. Mechanism involved in the luminescence has been discussed with the help of schematic representation, energy level diagram and chromaticity diagram. The prepared phosphors are suitable for biological labeling due to their dispersible capacity in different liquids (ethanol, phosphate buffered saline and water). Abstract: Tetragonal SrMoO4 :Eu 3+ downconverting phosphors functionalized with ethylene glycol have been synthesized via three different preparation techniques (urea hydrolysis, ammonia hydrolysis and hydrothermal methods). The developed phosphor shows strong red photoluminescence emission via electric dipole 5 D0 → 7 F2 transition and other weak transitions ( 5 D1 → 7 F1, 5 D0 → 7 F1, 5 D0 → 7 F3 and 5 D0 → 7 F4 ) by using three excitation wavelengths of 260, 395 and 464 nm. For the first time, a comprehensive discussion have been given for indirect and direct excitation for as-prepared phosphor prepared by the three different techniques. The needle imbedded spherical particles, elliptical shaped particles and orange carpels shaped particles have been obtained from the urea, ammonia and hydrothermal methods, respectively. The calculated quantum yields are found to be 7.5, 6.1 and 9.3% for urea, ammonia and hydrothermal based synthesized phosphors, respectively. The prepared phosphors are suitable for biological labeling due to their dispersible ability in different liquids (ethanol, phosphate buffered saline and water).